Modern Financial Market Theory~– A Critique Based on the Logic of Human Action - Thorsten Polleit (Credit and Capital Markets – Kredit und Kapital, 2021)
The modern financial market theory (MFMT)~– based on the efficient market hypothesis, rational expectation theory, and modern portfolio theory~– has become the standard approach in financial market economics. In this article, the MFMT will be critically reviewed using the logic of human action (or: praxeology) as an epistemological metatheory. It will be shown that the MFMT exhibits (praxeo-)logical deficiencies so that it cannot provide investors with well-founded decision-making support in real-world financial markets.
Keywords: G140; G41; B4; B41; E3; G1; G110; G14; 330; Efficient Market Hypothesis; Rational Expectation Theory; Modern Portfolio Theory; Capital Asset Pricing Model; Economic Methodology; Logic of human action; Austrian Economics